(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study analyzes the influence of Perceived Usefulness, Perceived Ease of Use, and Facilitating Conditions on Purchase Decisions among users of the Shopee e-commerce application in Sidoarjo. Employing a quantitative approach, the results indicate that Perceived Usefulness and Perceived Ease of Use have a positive and significant impact on Purchase Decisions, while Facilitating Conditions do not exhibit a significant influence. The findings imply the crucial role of application quality and user-friendliness in enhancing the effectiveness of purchase decisions. Recommendations involve technical improvements to enhance the impact of facilitating conditions. This research provides insights into factors affecting purchase decisions in the e-commerce context, laying the groundwork for further development to enhance user experience and the purchase decision-making process.